Sterol 27-Hydroxylase Polymorphism Significantly Associates With Shorter Telomere, Higher Cardiovascular and Type-2 Diabetes Risk in Obese Subjects - Pavanello, Sofia; Angelici, Laura; Hoxha, Mirjam; Cantone, Laura; Campisi, Manuela; Tirelli, Amedea Silvia; Vigna, Luisella; Pesatori, Angela Cecilia; Bollati, Valentina (Frontiers in Endocrinology, 2018)
Background/objectives The pathologic relationship linking obesity and lipid dismetabolism with earlier onset of aging-related disorders, including cardiovascular disease (CVD) and type-2 diabetes (T2D), is not fully elucidate. Chronic inflammatory state, in obese individuals, may accelerate cellular aging. However, leukocyte telomere length (LTL), the cellular biological aging indicator, is elusively linked with obesity. Recent studies indicate that sterol 27-hydroxylase (CYP27A1) is an emerging antiatherogenic enzyme, that, by converting extrahepatic cholesterol to 27-hydroxycholesterol, facilitates cholesterol removal via high-density lipoprotein-cholesterol (HDL-C). We tested the hypothesis that obese subjects who carry at least three copies of CYP27A1 low-hydroxylation (LH) activity genome-wide-validated alleles (rs4674345A, rs1554622A, and rs4674338G) present premature aging, as reflected in shorter LTL and higher levels of CVD/T2D risk factors, including reduced HDL-C. Subjects/methods Obese subjects from SPHERE project n = 1,457; overweight [body mass index (BMI) 25–30 kg/m2] 65.8% and severe-obese (BMI > 30 kg/m2) 34.2% were characterized for the presence from 0 to 6 LH-CYP27A1 allele copy number. Univariate and multivariable sex–age–smoking-adjusted linear-regression models were performed to compare CVD/T2D risk factors and biological aging (LTL) in relation to the combined BMI-LH groups: overweight-LH: 0–2, overweight-LH: 3–6, severe-obese-LH: 0–2, and severe-obese-LH: 3–6. Results Higher LTL attrition was found in severe-obese than overweight individuals (p < 0.001). Multivariable model reveals that among severe-obese patients those with LH: 3–6 present higher LTL attrition than LH: 0–2 (p < 0.05). Univariate and multivariable models remarkably show that insulin resistance is higher both in overweight-LH: 3–6 vs overweight-LH: 0–2 (p < 0.001) and in severe-obese-LH: 3–6 vs severe-obese-LH: 0–2 (p < 0.0001), and HDL-C is lower in overweight-LH: 3–6 than overweight-LH: 0–2 (p < 0.05 and p < 001). Finally, most of the well-known (i.e., blood pressure, heart rate, waist to hip, triglycerides, and HDL-C) and novel CVD risk factors [i.e., inflammation markers (C-reactive protein, leukocytes, and chemoattractant protein-1), fibrinogen, and glucose homeostasis (i.e., insulin resistance, and glycated hemoglobin)] are substantially (p < 0.0001) altered in severe-obese-LH: 0–2 vs overweight-LH: 0–2, pointing to the fact that obesity leads to worsen the CVD/T2D risk factor profile. Conclusion Our study supports evidence that CYP27A1 genetic characterization identifies persons at higher risk to develop CVD and T2D, on which better converge preventive measures, and opens new perspectives on mechanisms that link obesity with aging-related disorders.